Historical Review on Genetic Analysis in Hemophilia A - Oldenburg, Johannes; Pezeshkpoor, Behnaz; Pavlova, Anna (Seminars in Thrombosis and Hemostasis, 2014)
Molecular genetic analysis is widely applied in inherited bleeding disorders. The outcome of genetic analysis allows genetic counselling in affected families and helps to find a link between the genotype and phenotype. Genetic analysis in hemophilia A (HA) has tremendously improved in the past decades. Many new techniques and modifications as well as analysis software have become available, which has enabled genetic analysis and interpretation of data to become faster and more accurate. The advances in mutation detection strategies facilitate the identification of the causal mutation in up to 97% of patients with HA. This review discusses the milestones in genetic analysis of HA and highlights the importance of identification of the causative mutations for genetic counseling and particularly for the interpretation of the clinical presentation of HA patients.
Keywords: hemophilia A; genetic analysis; F8 gene mutations; historic overview